Non-operative management of iatrogenic colonic perforation after percutaneous cholecystotomy. Issue 12 (20th December 2018) - Musonza, Tashinga; Chai, Christy Y
Abstract: The management of iatrogenic colonic perforation encountered during percutaneous cholecystotomy tube placement is not well reported. It is unclear as to whether an operative versus a conservative approach is ideal for this complication. We therefore present our case report to spur a discussion on patient selection, interval follow-up and call for future studies regarding this uncommon complication.